2005
DOI: 10.1038/sj.gene.6364264
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-174-genotype, sepsis and cerebral injury in very low birth weight infants

Abstract: We investigated the association between the interleukin 6 (IL-6)-174-genotype and unfavorable outcomes in preterm infants since it has been reported that the IL-6-174GG-genotype is associated with increased susceptibility to sepsis, and the IL-6-174CC-genotype is more common in preterm infants with severe intraventricular hemorrhage (IVH). We studied 1206 preterm infants with a birth weight below 1500 g. In contrast to previously published data, the frequency of IVH grade IV, periventricular leukomalacia, vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 8 publications
(11 reference statements)
1
36
0
Order By: Relevance
“…Five articles that reported six cohort studies fulfilled the review eligibility criteria (table 1). 4 5 79 Two studies were reported in a single publication 8. Most studies were based in neonatal intensive care settings in Europe where participating infants were mostly of Caucasian ethnic ancestry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five articles that reported six cohort studies fulfilled the review eligibility criteria (table 1). 4 5 79 Two studies were reported in a single publication 8. Most studies were based in neonatal intensive care settings in Europe where participating infants were mostly of Caucasian ethnic ancestry.…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that screening VLBW newborn infants for this polymorphism may allow antimicrobial prophylaxis to be targeted to infants at highest risk of developing sepsis 6. However, subsequent genetic association studies have reported conflicting results 79…”
mentioning
confidence: 99%
“…In addition, IL-6 -174 CC genotype was associated with disability at 2 or 5 1 ⁄2 y of age (12). Quite contrary, Göpel et al (13) did not find any association between intraventricular hemorrhage (IVH) and periventricular leukomalacia (PVL) and IL-6 -174 genotypes. In addition, in the only available study of IL-6 -572 polymorphism, IL-6 -572 C genotype was reported to associate with less optimal neurodevelopmental performance at 2 y of corrected age and at 5 1 ⁄2 y of age in preterm infants (14).…”
mentioning
confidence: 86%
“…Furthermore, IL-6 polymorphism conferred an increased risk for PTD [46] and further studies suggested that the IL6-174 GG genotype was associated with higher risk for bacterial sepsis in preterm infants [50]. This finding was initially confirmed by another group [51 ] but could not be reproduced by a larger subsequent study from the same group [52,53 ].…”
Section: Interleukin-6mentioning
confidence: 75%